Does death anxiety moderate the adequacy of retirement savings? Empirical evidence from 40-plus clients of Spanish financial advisory firms - Pablo Garmendia; Gabriela Topa; Teresa Herrador; Montserrat Hernández (International Journal of Financial Studies, 2019)
This three-wave study analyses the mediating role of financial behavior in the relationship between financial goals and retirement saving adequacy, and the moderating role of Death anxiety. The participants in the study (N = 276) were 40-plus Spanish clients of financial advisory firms. The results show that the relationship between financial goals and retirement saving adequacy is, in fact, mediated by financial behavior. We also found that death anxiety moderates the financial behavior-retirement saving adequacy relationship. The theoretical and practical implications of the study for design are discussed at the end of the paper.
Keywords: G12; G14; G17; 330; death anxiety; financial goals; retirement; financial behavior